On the interaction between the island divertor heat fluxes, the scrape-off layer radial electric field and the edge turbulence in Wendelstein 7-X plasmas. (1st February 2023) - Maragkoudakis, E.; Carralero, D.; Estrada, T.; Windisch, T.; Gao, Y.; Killer, C.; Jakubowski, M.; Puig Sitjes, A.; Pisano, F.; Sándor, H.; Vecsei, M.; Zoletnik, S.; et al.
Abstract: The formation of the radial electric field, E r in the scrape-off layer (SOL) has been experimentally studied for attached divertor conditions in stellarator W7-X. The main objective of this study is to test the validity in a complex three-dimensional (3D) island divertor of simple models, typically developed in tokamaks, relating E r in the SOL to the sheath potential drop gradient at the target. Additionally, we investigate the effect of the edge E r shear on the reduction of density fluctuation amplitude, a well-established phenomenon according to the existing bibliography. The main diagnostic for measurements in the SOL is a V-band Doppler reflectometer that can provide the measurement of the E r and density fluctuations with good spatial resolution. 3D measurements of divertor parameters have been carried out using infrared cameras, with the exponential decay length of the divertor heat flux ( λ q ) resulting in a suitable proxy for the model-relevant λ T, the exponential decay length of the temperature at the divertor. In the investigated attached regimes, it is shown for the first time that the formation of the E r in the SOL depends on parameters at the divertor, following a E r ∝ T e / λ q qualitatively similar to that found in a tokamak. Then, from the analyzed plasmas, the observed E r shear at the edge is linked to a moderate local reduction of the amplitude of density fluctuations.